Association of Signal Transducer and Activator of Transcription 4 rs10181656 Polymorphism With Rheumatoid Arthritis and Systemic Sclerosis in Khuzestan Province in Southwestern Iran - Fatemeh GHANAVATI,; Seyed Reza Kazemi NEZHAD,; Mohammad Reza HAJJARI,; Mohammad Reza AKHOOND, (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the association of polymorphism rs10181656 (C>G) of signal transducer and activator of transcription 4 (STAT4) gene with rheumatoid arthritis (RA) and systemic sclerosis (SSc) in the southwest of Iran as well as the probable relationship between the polymorphism with clinical features and disease activity parameters in both diseases. Patients and methods: A total of 200 patients (120 with RA [21 males, 99 females; mean age 44.83 years; range, 16 to 75 years] and 80 with SSc [13 males, 67 females; mean age 44.3 years; range, 30 to 75 years]) and 120 healthy controls (25 males, 95 females; mean age 46.93 years; range, 30 to 75 years) were recruited in this study. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism. A set of genotypes was confirmed by sequencing. Results: A statistically significant association was detected between STAT4 rs10181656 polymorphism and RA (p=0.007). No significant correlation was detected between STAT4 rs10181656 polymorphism and SSc (p=0.357). None of the clinical features (anti-cyclic citrullinated peptide, rheumatoid factor) or disease activity parameters (limited cutaneous SSc, diffuse cutaneous SSc) showed any correlation with the genotype distribution of the STAT4 rs10181656 polymorphism in RA or SSc patients. Conclusion: Our findings suggest an association between RA susceptibility and STAT4 rs10181656 polymorphism. However, no significant association was found between the mentioned polymorphism and SSc. Clinical features and disease activity parameters did not show any association with the polymorphism.